VaR and tail dependence between the US and Asian stock exchange indices - An EGARCH-copula approach - Ji Ma (2018)
© 2017 The authors and IOS Press. All rights reserved. This paper uses the eGARCH-Copula model to examine the tail dependence and Value at Risk (VaR) of the log returns of the US and Asian exchange indices as pairs of portfolio in three periods: before, in and after finance crisis. The results indicated that the eGARCH-Copula model works well on measuring the tail dependence and VaR between the US and Asian stock market; and after finance crisis, the dependence structure changed including on tail dependence and VaR.